Ansvarlighet i samarbeidet mellom ansatte og beboere i et kommunalt bofellesskap - Mækelæ, Jonny (Nordisk tidsskrift for helseforskning, 2015)
St.prp.1 (2004–2005) emphasized that local authorities must take steps to ensure people with severe mental problems have access to adapted housing. As part of this process, the municipality of Bodø built facilities that were opened in spring 2008. There were engaged professional health workers, whose task was to assist and support the residents to cope with their everyday challenges. The findings of this study show that different constellations of responsibility are essential for the phenomenon of cooperation between staff and residents in a supported housing arrangement. The most important conclusion is that the residents appreciated and were dependent on the employees’ support and care to cope with everyday situations. At the same time this could cause unfortunate dependence between the two parts. Self –determination seem to be essential factors for residents to take initiative and be active, and for residents to engage themselves in personal change projects.